Towards an Open-Domain Framework for Distilling the Outcomes of Personal Experiences from Social Media Timelines - Olteanu, Alexandra; Varol, Onur; Kiciman, Emre (International Conference on Web and Social Media (ICWSM), 2016)
Millions of people share details about their real-world experiences on social media. This provides an opportunity to observe the outcomes of common and critical situations and actions for individual and societal beneﬁt. In this paper, we discuss our efforts to design and build an open-domain framework for mining the outcomes of any given experience from social media timelines. Through a number of example situations and actions across multiple domains, we discuss the kinds of outcomes we are able to extract and their relevance.